Characterization and In Vitro Digestion Kinetics of Purified Pulse Starches: Implications on Bread Formulation - Oluwatoyin O. Sangokunle; Sarah G. Corwin; Bruce R. Hamaker (Foods)
This study investigated the contribution of pulse starches (PSs) to the slowly digestible starch (SDS) properties observed in pulses. Purified pulse starches from 17 commonly consumed pulses were examined, focusing on their digestion kinetics using a pancreatic alpha-amylase (PAA) and rat intestinal acetone powder (RIAP) mixture. Chickpea starch, exhibiting a slow digestibility profile, was incorporated as an ingredient to confer slow digestibility to refined wheat flour bread. Our findings reveal that some PSs exhibited low digestibility when gelatinized (100 °C, 30 min) and retrograded (7 days, 4 °C). Rapid retrogradation was observed in starch from chickpeas, lentils, field peas, adzuki beans, navy beans, large lima beans, and great northern beans. The incorporation of chickpea starch into fortified bread significantly improved its slow digestibility properties. This study reveals the potential of pulse starch as a promising functional ingredient for baked products, related to the faster retrogradation of many pulse-sourced starches. These findings contribute valuable insights into the slow digestibility attributes of pulse starches for developing food products with enhanced nutritional profiles.